2019
DOI: 10.1136/bmjopen-2018-022278
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with peripheral intravenous cannulation first-time insertion success in the emergency department. A multicentre prospective cohort analysis of patient, clinician and product characteristics

Abstract: ObjectivesThis study aimed to identify the incidence of and factors associated with peripheral intravenous catheter/cannula (PIVC) first time insertion success (FTIS) in the emergency department (ED).DesignProspective cohort study.SettingTwo tertiary EDs in Western Australia.Participants879 ED patients.Primary outcomeTo identify factors affecting FTIS using univariate and multivariate logistic regression modelling. We created four models:patient factors only; clinician factors only; products and technology fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
2
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 25 publications
1
47
2
6
Order By: Relevance
“…This conclusion is in line with Rippey et al [36], who associated clinical experience with the ability to predict difficulty, based on a prior assessment of vascular access. In addition, numerous studies have found the visibility and, above all, the palpability of the vein, according to the nurse's assessment, to be of great significance [22][23][24]37,38]. In our sample, the non-identification of palpable veins after the application of a tourniquet was found to be an independent risk factor for DPIVC (OR 2.35, 95% CI 1.65 to 3.36).…”
Section: Discussionmentioning
confidence: 62%
“…This conclusion is in line with Rippey et al [36], who associated clinical experience with the ability to predict difficulty, based on a prior assessment of vascular access. In addition, numerous studies have found the visibility and, above all, the palpability of the vein, according to the nurse's assessment, to be of great significance [22][23][24]37,38]. In our sample, the non-identification of palpable veins after the application of a tourniquet was found to be an independent risk factor for DPIVC (OR 2.35, 95% CI 1.65 to 3.36).…”
Section: Discussionmentioning
confidence: 62%
“…To assess the A-DM’s criteria and construct validity, the total scores obtained were correlated with patient and procedural-related variables that are identified in the literature as hypothetically associated with intravenous access difficulty ( Table 4 ) [ 2 , 3 , 6 , 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several correlation analyses were conducted to further quantify the A-DM’s validity [ 22 ], using a comprehensive list of patient and procedural-related variables described in the literature as potentially associated with difficult peripheral intravenous access [ 2 , 3 , 6 , 23 , 24 ]. Regarding patient-related variables, the A-DM total scores correlated significantly with patient’s age, body mass index, Type-2 Diabetes diagnosis, and previous antineoplastic treatment (such as chemo or radiotherapy).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 Success rates of SPC insertion on the first attempt ranging from 86% to 96% have been reported. 4 6 In the emergency department, where the procedure is frequently performed in a fast-paced clinical environment, first-attempt success tends to be lower, up to 73%. 7 Repeated needle-insertion attempts may cause patient psychological complications, such as distress and anxiety, as well as pain, vein injury, and enhanced risk of infection.…”
mentioning
confidence: 99%